(untitled) (Journal of Hama University, 2024)
The research was conducted on (6) local dogs, aged (2-5) years and weighing (18-29) kg. They were placed in special boxes for dogs and under the same health and nutritional conditions at the College of Veterinary Medicine at the University of Hama. The six dogs underwent investigative laparotomy under general anesthesia, where xylazine was used in combination with ketamine according to scientific principles. After completing the laparotomy, clinical indicators (heart rate - respiratory rate - temperature), hematological indicators (red blood cell count, white blood cell count, and platelet count) and behavioral and sensory indicators (pain relief indicators) were recorded (degree of moaning - Degree of fatigue – difficulty of breathing) in all dogs before the surgical procedure (before giving any sedative or general anesthesia) and also after the surgical procedure (after giving ketorolac) (1 hour - 3 hours - 6 hours - 12 hours - 1 day - 2 days – 3( days. The results showed slight significant differences in clinical and hematological indicators and clear significant differences P<0.05 when using ketorolac doses of 0.5 mg/kg , with an interval of 6 hours between each dose for 3 days. In terms of pain relief after laparotomy. It is concluded from this research that the use of ketorolac compound in terms of post-operative analgesia in dogs was effective and safe and had no side effects.